COLLABORATION ON IMPROVING SOP AND SOM UNIT SAVINGS AND LOANS COOPERATIVE KUD MINATANI BRONDONG LAMONGAN: KOLABORASI PENYEMPURNAAN SOP DAN SOM UNIT SIMPAN PINJAM KOPERASI KUD MINATANI BRONDONG LAMONGAN - Suyitno Suyitno; Yulie Wahyuningsih (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The existence of the Koperasi KUD Minatani Brondong Savings and Loans Unit is a financial service institution that is quite large and is trusted by the people of Lamongan Regency and its surroundings, this is marked by an increase in the number of members, an increase in loan requests and a high amount of public fund deposits. Expanding the scope of services to respond to public interest, the USP Koperasi KUD Minatani developed services by opening Karanggeneng, Modo, Kedungpring, Ngimbang, Lohgung, Banjarwati, Laren, and Babat branches in the administrative area of ​​Lamongan Regency. Understanding the importance of efforts to institutionalize structured and massive rules as well as efficient and effective control of all resources, USP Koperasi KUD Minatani collaborates and assists to improve Standard Operating Procedures and Standard Operational Management by taking into account Vision and Mission and Referring to Permenkop number: 16/PER/M.KUKM/IX/2015 concerning Implementation Business Activities of Savings and Loans and Sharia Financing by Cooperatives. Activities are carried out through substantial participatory methods through the stages of FGD, outreach, mentoring as well as monitoring and evaluation. Activities involve Management, Supervisors, USP Managers and Members, by placing partners as the main actors and having an equal position with community service implementers. The results of the implementation of Collaborative activities to improve quality, implementable, objective and visionary standard operating procedures and operational management standards in an effort to realize the USP of Koperasi KUD Minatani as a financial service institution that is professional, innovative, accountable and competitive